Performance optimisation of a CNC machine through exploration of timed state space. (13th October 2010) - Mujica, Miguel A.; Piera, Miquel Angel
Flexible production units provide very efficient mechanisms to adapt the type and production rate according to fluctuations in demand. The optimal sequence of the different manufacturing tasks in each machine is a challenging problem that can deal with important productivity benefits. In this paper a Coloured Petri Net model of an eyeglass flexible production machine is presented. The problem of finding an optimal sequence for this machine is faced using an algorithm which uses the model together with the exploration of the state space to find an optimal or close to the optimal scheduling that minimises the makespan of different workloads.